A phase Ib study of sonidegib (LDE225), an oral small molecule inhibitor of smoothened or Hedgehog pathway, in combination with docetaxel in triple negative advanced breast cancer patients: GEICAM/2012–12 (EDALINE) study - Ruiz-Borrego, Manuel; Jimenez, Begoña; Antolín, Silvia; García-Saenz, Jose A.; Corral, Jesús; Jerez, Yolanda; Trigo, José; Urruticoechea, Ander; Colom, Helena; Gonzalo, Nuria; Muñoz, Carmen; Benito, Sara; et al. (Investigational new drugs, 2019)
Summary Up-regulation of the Hedgehog (Hh) pathway is implicated in the genesis of a wide range of tumors including triple negative breast cancer (TNBC). Sonidegib is a potent and selective oral inhibitor of Smo, a key component of the Hh signaling pathway. We designed a phase I clinical study to explore the combination of sonidegib plus docetaxel (fixed dose at 75 mg/m 2 ) in advanced TNBC patients. The primary objective was to ascertain the combination’s maximum tolerated dose and the recommended phase II dose (RP2D), based on dose limiting toxicities (DLTs) in the first 2 cycles. A standard “3 + 3” design was followed including three dose levels (DL) of sonidegib: 400 mg (DL1), 600 mg (DL2), and 800 mg (DL3). Twelve patients were included. Sonidegib 800 mg orally q.d. plus docetaxel 75 mg/m 2 given intravenously on day 1 of 21-day cycles was established as the RP2D. No DLTs were observed at any DL. The median number of administered cycles at DL3 was 8 (range: 6 to 9). Grade 3 adverse events (AEs) at DL3 were neutropenia (66.7%), CPK increase (33.3%), leukopenia (33.3%), and paresthesia (33.3%), grade 4 AEs were not reported at this DL. At the RP2D, the combination showed antitumor activity in three out of 10 patients with measurable disease. Median time to progression for the overall study was 42.5 days (95% Confidence Interval: 29–155), and 188 days at DL3. No drug-to-drug interactions between sonidegib and docetaxel were found in the PK assessment. Trial Registration: EudraCT study number: 2013–001750-96. Study GEICAM/2012–12. TRIAL REGISTRATION: EudraCT study number: 2013-001750-96. Study GEICAM/2012-12. ClinicalTrials.gov: NCT02027376